Alih Aksara dan Alih Bahasa Teks Paparan Adat Limbago Alam Minangkabau - Serly Feblinda; Nurizzati Nurizzati (Faculty of Languages and Arts, Universitas Negeri Padang, 2020)
This study aims to describe the physical description form of the Paparan Adat Limbago Alam Minangkabau Dan Sejarah Asal-Usul Pertalian Negeri-Negeri Disusun Oleh Wahid Datuak Rajo Basa Qadi Salamat manuscript; to explain the form of the transcription of the text of Paparan Adat Limbago Alam Minangkabau Dan Sejarah Asal-Usul Pertalian Negeri-Negeri Disusun Oleh Wahid Datuak Rajo Basa Qadi Salamat in the text of the Paparan Adat Limbago Alam Minangkabau Dan Sejarah Asal-Usul Pertalian Negeri-Negeri Disusun Oleh Wahid Datuak Rajo Basa Qadi Salamat; to display the form of the translation of the text of the Paparan Adat Limbago Alam Minangkabau Dan Sejarah Asal-Usul Pertalian Negeri-Negeri Disusun Oleh Wahid Datuak Rajo Basa Qadi Salamat text in the Paparan Adat Limbago Alam Minangkabau Dan Sejarah Asal-Usul Pertalian Negeri-Negeri Disusun Oleh Wahid Datuak Rajo Basa Qadi Salamat manuscript. This research is philology research. This research resulted in (1) description of Paparan Adat Limbago Alam Minangkabau Dan Sejarah Asal-Usul Pertalian Negeri-Negeri Disusun Oleh Wahid Datuak Rajo Basa Qadi Salamat manuscript; (2) the transfer of Paparan Adat Limbago Alam Minangkabau Dan Sejarah Asal-Usul Pertalian Negeri-Negeri Disusun Oleh Wahid Datuak Rajo Basa Qadi Salamat’s text which is transcribed from Arabic-Malay script to Latin script; (3) the transfer of the text of the Paparan Adat Limbago Alam Minangkabau Dan Sejarah Asal-Usul Pertalian Negeri-Negeri Disusun Oleh Wahid Datuak Rajo Basa Qadi Salamat text which was translated from Malay into Indonesian.